2006
DOI: 10.1166/jnn.2006.146
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Platinum Clusters on Surface-Modified Tobacco Mosaic Virus

Abstract: Nanoscaled Pt conductors were prepared from genetically engineered Tobacco mosaic virus (TMV) templates through Pt cluster deposition on the outer surface of the TMV. Pt clusters were synthesized and deposited on the engineered TMV with surface-exposed cysteine via the in situ mineralization of hexachloroplatinate anions. This deposition was driven by the specific binding between thiols and the solid metal clusters. In addition, Pt-thiolate adducts are suggested to form on the engineered TMV in aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 19 publications
3
96
0
1
Order By: Relevance
“…Inorganic deposition onto these bio-templates has been accomplished using a variety of methodologies including chemical crosslinking, genetic engineering, and electroless plating, resulting in the deposition of numerous inorganic compounds including metal particles, silica, metal oxides, and metal sulfides [7][8][9][10]. Virusassembled inorganic nanostructures have been fashioned into conductive nanowires, field effect transistors, memory device components, and battery electrodes [11][12][13][14]. From these studies it is clear that inherent biologically properties of viruses, includ-* Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic deposition onto these bio-templates has been accomplished using a variety of methodologies including chemical crosslinking, genetic engineering, and electroless plating, resulting in the deposition of numerous inorganic compounds including metal particles, silica, metal oxides, and metal sulfides [7][8][9][10]. Virusassembled inorganic nanostructures have been fashioned into conductive nanowires, field effect transistors, memory device components, and battery electrodes [11][12][13][14]. From these studies it is clear that inherent biologically properties of viruses, includ-* Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Coating of materials onto the TMV surface has relied on electrostatic interactions in aqueous solvents [8,12,17,18]. In these instances, the solution pH was adjusted so the charge of the coating particle and that of the biological template were mutually attractive.…”
Section: Introductionmentioning
confidence: 99%
“…The symmetrical arrangement of the outer coat proteins of the viral particles makes them attractive scaffolds for polyvalent display of a variety of functional groups for various applications [32][33][34][35]. In the past two decades, taking advantages of distinctive chemical and biological properties of plant viruses, new materials with unique structural features have been developed for a wide range of applications, including electronics, drug delivery, imaging, gene therapy, and immunotherapy [35][36][37][38][39][40][41][42][43][44][45][46][47]. Recent studies have reported that cowpea mosaic virus (CPMV) can interact with the mammalian cells due to the presence of two highly specific CPMV-binding proteins present in certain mammalian cells [48].…”
Section: Introductionmentioning
confidence: 99%
“…3c shows that small Pd NPs are highly crystalline with spacings of 0.23 nm, which closely matches the (1 1 1) interplanar distance of FCC palladium metal [32]. The formation of Pd-insulin complexes is likely because insulin peptides contain several Cys-rich regions that are known to enhancing the "biosorption" [33,34]. Moreover, carboxyl and amino acid side chains such as serine are also known to have strong complexation abilities with metal precursors.…”
Section: Biosynthesis Of Palladium Nanoparticlesmentioning
confidence: 58%